2018
DOI: 10.1002/ece3.4602
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation trends over eleven years on mountain summits in NW Argentina

Abstract: As global climate change leads to warmer and dryer conditions in the central Andes, alpine plant communities are forced to upward displacements following their climatic niche. Species range shifts are predicted to have major impacts on alpine communities by reshuffling species composition and abundances. Using a standardized protocol, we surveyed alpine plant communities in permanent plots on four high Andean summits in NW Argentina, which range from 4,040 to 4,740 m a.s.l. After a baseline survey in 2006–2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 57 publications
(87 reference statements)
5
24
1
10
Order By: Relevance
“…Most of the AR2 species show a clear prevalence of colonisations over disappearances (Table 1, Tables S1, S4, S5), suggesting a leading-edge expansion of this species group, similar to previous observations of elevational and latitudinal range shifts (Carilla et al 2018;Parmesan and Yohe 2003;Rumpf et al 2018). Among the common AR2 species, Silene exscapa exhibited a moderate but steady increase and hardly any losses, whereas others like Festuca intercedens showed contrasting changes with both numbers of colonisations and disappearances significantly increasing from the first to the second decade (Tables S1, S4, S5).…”
Section: Trailing-edge Contraction Of Crypophilic Species and Leading-edge Expansion Of Lower-elevation Speciessupporting
confidence: 87%
“…Most of the AR2 species show a clear prevalence of colonisations over disappearances (Table 1, Tables S1, S4, S5), suggesting a leading-edge expansion of this species group, similar to previous observations of elevational and latitudinal range shifts (Carilla et al 2018;Parmesan and Yohe 2003;Rumpf et al 2018). Among the common AR2 species, Silene exscapa exhibited a moderate but steady increase and hardly any losses, whereas others like Festuca intercedens showed contrasting changes with both numbers of colonisations and disappearances significantly increasing from the first to the second decade (Tables S1, S4, S5).…”
Section: Trailing-edge Contraction Of Crypophilic Species and Leading-edge Expansion Of Lower-elevation Speciessupporting
confidence: 87%
“…For example, through this study, 5 species in SC (Acaena platyacantha, Benthamiella spegazziniana, Philippiella patagonica, V. moyanoi, and V. magellanica) and 3 in TF (A. antarctica, S. alloeophyllus var. alloeophyllus, and S. humifusus) were found outside of their expected elevation ranges, as was reported in other GLORIA works [17].…”
Section: Discussionsupporting
confidence: 86%
“…These authors argue that the increase in species richness in those Australian alpine areas could be explained by the influence of other environmental factors (e.g., rainfall, microsite availability, species interactions, and dispersal/recruitment potential in the regional species pool) rather than climate warming. The influence of ENSO has already been demonstrated in South American alpine environments [17]. We found contrasting effects of ENSO in soil temperature and growing season in the two sites of the present study, that found inverse trends (e.g., higher soil temperatures in SC, but lower soil temperatures in TF during a La Niña event).…”
Section: Discussionsupporting
confidence: 55%
“…Our results suggest that the use of thermal niche traits could be an effective approach for assessing the warming‐induced transformation of tropical alpine plant species compositions and the risk of biodiversity losses by means of repeated permanent plot surveys. Given that climate change impacts could be nonlinear (Carilla et al, ), it is important to strengthen long‐term ecological observation networks. All plots used in this study were established as permanent plots of the GLORIA‐Andes network.…”
Section: Discussionmentioning
confidence: 99%